Mondo Macabro as trashy/cult film archive the case of classic Indonesian exploitation cinema - Imanjaya, Ekky (Plaridel, 2018)
Access online through this link: https://www.plarideljournal.org/article/mondo-macabro-as-trashy-cult-film-archive-the-case-of-classic-indonesian-exploitation-cinema